BEMGIE: Belgian Economy in a Macro General and International Equilibrium model - Gregory De Walque; Thomas Lejeune; Ansgar Rannenberg; Rafael Wouters (National Bank of Belgium, 2023)
This paper outlines the three-country New Keynesian Dynamic Stochastic General Equilibrium model of the National Bank of Belgium. The model is named BEMGIE for Belgian Economy in a Macro General and International Equilibrium model. It features imperfect market competition, standard real and nominal rigidities, local currency pricing, energy in consumption and oil and foreign inputs in production. The model is estimated using Bayesian econometric techniques on Belgian, euro area and US data. BEMGIE is designed to provide quantitative simulations of macroeconomic shocks and policies, and to be used in the context of the Eurosystem projection exercises.
Keywords: E10; E17; E30; E40; E52; F41; F45; F47; C11; C32; C51; 330; DSGE model; Open economy model; Multi-country model; International spillovers; Monetary policy; Exchange rate pass-through; Bayesian estimation